2017
DOI: 10.1371/journal.pone.0186413
|View full text |Cite
|
Sign up to set email alerts
|

Psychological well-being in elderly adults with extraordinary episodic memory

Abstract: ObjectivesThe Northwestern University SuperAging Program studies a rare cohort of individuals over age 80 with episodic memory ability at least as good as middle-age adults to determine what factors contribute to their elite memory performance. As psychological well-being is positively correlated with cognitive performance in older adults, the present study examined whether aspects of psychological well-being distinguish cognitive SuperAgers from their cognitively average-for-age, same-age peers.MethodThirty-o… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

5
29
0
1

Year Published

2018
2018
2023
2023

Publication Types

Select...
5
3

Relationship

1
7

Authors

Journals

citations
Cited by 53 publications
(35 citation statements)
references
References 33 publications
5
29
0
1
Order By: Relevance
“…These themes align well with the suggested importance of participating in cognitively stimulating activities for maintaining cognitive health in older age (Festini, McDonough, & Park, 2016;Hultsch, Hertzog, Small, & Dixon, 1999;Park et al, 2014;Singh-Manoux, Richards, & Marmot, 2003;Wilson et al, 2002;Wilson, Scherr, Schneider, Tang, & Bennett, 2007). The descriptions of the participants are consistent with our recent report examining psychological wellbeing, where 31 SuperAgers endorsed higher "positive social relationships with others" compared to their similarly aged cognitively average peers (Cook Maher et al, 2017). While all SuperAging participants in this report showed IQ scores in the high average to superior range, formal education varied from 12 to 18 years.…”
Section: Discussionsupporting
confidence: 86%
“…These themes align well with the suggested importance of participating in cognitively stimulating activities for maintaining cognitive health in older age (Festini, McDonough, & Park, 2016;Hultsch, Hertzog, Small, & Dixon, 1999;Park et al, 2014;Singh-Manoux, Richards, & Marmot, 2003;Wilson et al, 2002;Wilson, Scherr, Schneider, Tang, & Bennett, 2007). The descriptions of the participants are consistent with our recent report examining psychological wellbeing, where 31 SuperAgers endorsed higher "positive social relationships with others" compared to their similarly aged cognitively average peers (Cook Maher et al, 2017). While all SuperAging participants in this report showed IQ scores in the high average to superior range, formal education varied from 12 to 18 years.…”
Section: Discussionsupporting
confidence: 86%
“…Mezi další patří učení se novým věcem a kladení si výzev znamenajících určitou námahu, pro jejichž dosažení je nutné překonat vlastní pohodlnost a zajeté koleje (Lindquist et al, 2016). Pro SuperAgera je více obvyklé mít pevnou sociální síť -přátele, k nimž má důvěru, že pomohou, pokud bude pomoc potřebovat (Cook Maher et al, 2017).…”
Section: žIvotní Styl a Superagingunclassified
“…From 4,457 potentially relevant citations retrieved from electronic databases and searches of reference lists, nine (0.2%) studies met the inclusion criteria ( Figure 1). There were three studies on neuroimaging (Harrison et al, 2012;Cook et al, 2017;Dekhtyar et al, 2017), two on histological analysis (Gefen et al, 2015;Janeczek et al, 2017), one on plasma metabolites (Mapstone et al, 2017), and two on neuropsychological profile (Gefen et al, 2014;Cook Maher et al, 2017). One study reported findings that had been previously published, provided another specific outcome, namely apolipoprotein E (ApoE) status (Rogalski et al, 2013) (Table 1).…”
Section: Characteristics Of Included Articlesmentioning
confidence: 99%
“…Notably, high-performing older adults were described with different terms, namely "SuperAgers" (Harrison et al, 2012;Rogalski et al, 2013;Gefen et al, 2014;2015;Cook et al, 2017;Cook Maher et al, 2017;Janeczek et al, 2017), "Supernormals" (Mapstone et al, 2017), and "Optimal performers" (Dekhtyar et al, 2017). All definitions converged in classifying older adults according to their episodic memory performance.…”
Section: Characteristics Of Included Articlesmentioning
confidence: 99%